Carbon nanosol-induced assemblage of a plant-beneficial microbiome consortium - Lingtong Cheng; Jiemeng Tao; Zechao Qu; Peng Lu; Taibo Liang; Lijun Meng; Wei Zhang; Nan Liu; Jianfeng Zhang; Peijian Cao; Jingjing Jin (Journal of Nanobiotechnology, 2023)
Abstract Carbon nanosol (CNS) is a carbon-based nanomaterial that promotes plant growth; however, its functional mechanisms and effects on the microbiome are not fully understood. Here, we explored the effects of CNS on the relationship between the soil, endophytic microbiomes and plant productivity. CNS treatment increased the fresh biomass of tobacco (Nicotiana tabacum L.) plants by 27.4% ± 9.9%. Amplicon sequencing analysis showed that the CNS treatment significantly affected the composition and diversity of the microbial communities in multiple ecological niches associated with tobacco, especially the bulk soil and stem endophytic microbiome. Furthermore, the application of CNS resulted in enhanced network connectivity and stability of the microbial communities in different niches, particularly in the soil, implying a strengthening of certain microbial interactions. Certain potentially growth-promoting root endophytic bacteria were more abundant under the CNS treatment. In addition, CNS increased the abundance of some endophytic microbial functional genes known to enhance plant growth, such as those associated with nutrient metabolism and the plant hormone biosynthesis pathways. We isolated two bacterial strains (Sphingopyxis sp. and Novosphingobium sp.) that were enriched under CNS treatment, and they were confirmed to promote tobacco plant growth in vitro. These results suggested that CNS might, at least in part, promote plant growth by enriching beneficial bacteria in the microbiome. Graphical Abstract